PEMANFAATAN PEKARANGAN RUMAH SEBAGAI TEMPAT BUDIDAYA TANAMAN REMPAH DAN SAYUR MASYARAKAT DESA SAMINYAMAU - Manikome, Nonice; Erbabley, Baltazar Zadrak (MAANU: Jurnal Pengabdian Kepada Masyarakat, 2023)
The use of yard land is relatively minimal, a lot of yard land is used as idle land, a lot of yard land is only covered with grass. This of course results in minimal development of various innovations related to yard land and the unavailability of spices and vegetables for consumption by the community. Based on these reasons, community service activities were carried out in Saminyamau Village with the title Utilizing House Yards as a Place for Cultivating Spices and Vegetables. Community Service Activities will be held on June 29 2023, located in the Saminyamau Village Office Yard. In its implementation, the speaker conveyed some information on several techniques for cultivating vegetables and herbs that can be used, with the aim of optimizing the potential of yard land to meet the family's daily food needs and providing motivation for the community to make maximum use of yard land which, if it continues to be developed, can be used as a village business. to become a village that is independent of spices and vegetables.